MacDonald's party Labour identities and crisis, 1922-1931 - Howell, David, 1945- (Oxford University Press, 2002)
This study offers a detailed analysis of Labour in the 1920s, based on a wide variety of unpublished sources. The emphasis is on the variety of personalities within the party, demonstrating how disputes over identity made a crucial contribution to the 1931 crisis.